Fire regimes and structural changes in oak-pine forests of the Mogollon Highlands ecoregion: Implications for ecological restoration - Huffman, David W.; Floyd, M. Lisa; Hanna, Dustin P.; Crouse, Joseph E.; Fulé, Peter Z.; Sánchez Meador, Andrew J.; Springer, Judith D. (Forest ecology and management, 2020)
•Ponderosa pine forests of the Mogollon Highlands ecoregion are complex.•We reconstructed historical fire regimes and forest structure at five sites.•All sites showed evidence of frequent, low-severity fire regimes.•Forests were historically open with low densities of oak and ponderosa pine.•Without modern fires forests have become susceptible to type conversion. Ponderosa pine (Pinus ponderosa) forests occur at their warmer, drier environmental limits in the Mogollon Highlands ecoregion (MHE) of the Southwestern United States, and are commonly found in stringers or discrete stands that form ecotones with interior chaparral. These “rear edge” forests are likely to be highly vulnerable to rapid changes in structure and composition with climate warming, drought, and wildfire. There is increasing interest in understanding historical conditions, ecosystem changes, and restoration needs for MHE forests. However, comprehensive reconstruction analysis of fire regimes and stand structure has not been done for these systems, which differ from many montane ponderosa pine forests by having an abundance of understory shrubs. In this study we used demographic data from field plots, fire scar samples, and dendroecology to reconstruct historical fire regimes and landscape structure at ponderosa pine-dominated sites that spanned a range of environmental conditions on the Prescott and Tonto National Forests. We found strong evidence of historical surface fire regimes with mean fire intervals ranging 1.3–15.6 years across the five MHE sites during the period 1700–1879. We found very little evidence of historical high-severity fire at any study site. Historical forest structure was open with tree densities ranging 84.7–136.4 trees ha−1 and stand basal area (BA) ranging 4.5–8.4 m2 ha−1. Historical composition showed codominance of ponderosa pine, Arizona white oak (Quercus arizonica), Emory oak (Q. emoryi), and Gambel oak (Q. gambelii). Thus, oak species and likely other hardwoods were important historical components of these ecosystems. Contemporary forests are greater in stand density and BA by 359–703% and 285–502%, respectively, compared to historical estimates. In addition, we observed contemporary shifts in species composition. Changes related to disruption of historical fire regimes have increased susceptibility of ponderosa pine forests in the MHE to rapid shifts in structure and composition that may come about with climate change and high-intensity wildfire. Meeting fuels reduction and ecological restoration goals will be challenging for land managers due to vigorous regeneration responses of shrubs to tree thinning, prescribed burning, or other management activities. Managers will be required to balance attention to historical reference conditions, conservation of biological diversity, and needs for fuels management.